A plant design on sorbitol manufacture by catalytic hydrogenation of dextrose - Castro, Fermin V. (College of Engineering, 1963)
In connection with the policy of the Ferloure Manufacturing Corporation to utilize in a great extent the potential raw materials in this country, an economic evaluation on the manufacture of sorbitol from corn sugar by the catalytic hydrogenation process was authorized to determine the feasibility of establishing a sorbitol plant in the Philippines. This report includes a general description of the manufacturing process, together with illustrations and flowsheets showing the equipment and materials required for the production of sorbitol. Also included are the plant layout, a complete cost breakdown, and the breakeven chart.